OPPORTUNITIES AND CHALLENGES OF TOURISM MICRO-BUSINESS ‘DRIED FISH’ IN BARRU REGENCY: PUSH AND PULL FACTORS PERSPECTIVE - Junaid, Ilham (Politeknik Pariwisata NHI Bandung, 2022)
Tourism is only seen in macro businesses, whereas micro-businesses tend not to attract tourism stakeholders' attention. There are limited studies on the opportunities and challenges of tourism micro-business, especially those related to managing dried or salted fish. This study aims to 1) identify opportunities and challenges in managing the micro-business of dried fish; 2) analyse the sustainability factors of the micro-business of dried fish in the context of tourism; 3) propose a tourism micro-business management strategy. This study employs a qualitative approach by conducting field visits at dried fish sales locations in Barru regency in August and September 2022. The study reveals that the micro-business opportunity of dried fish could be an education-based tourism product. Educational tourism provides opportunities for tourists to learn about fishery products, the management of dried fish products, and sales to consumption by tourists. The challenges of micro-business are; managing and selling dried fish with the principles of hygiene and sanitation, decreasing sales, fish product packaging, understanding customer service; providing information on dried fish products; and product innovation. The decreasing number of dried fish sales can affect the sustainability of the dried fish micro business. Therefore, the stakeholders' role can help sustain the dried fish micro-business. This study proposes approaches for tourism micro-business management on the perspective of push and pull factors. Academics use the concept of push and pull factors in assessing tourist motivation. However, push and pull factors are also helpful in analysing micro-business management in the tourism sector.